Strategi Komunikasi Hadapi Penolakan Pemanfaatan Energi Nuklir sebagai Pembangkit Listrik di Indonesia - Syahdino Pratama; Satriani Aga Pasma; Mokhamad Hendayun; Isroil Samihardjo (Jurnal Ilmu Sosial dan Ilmu Politik)
One form of potential threat faced by Indonesia is an energy crisis that can disrupt national stability. However, the use of nuclear as an alternative source of clean energy through Nuclear Power Plants (PLTN) has not been realized until now. This research aims to identify the obstacles faced in the plan to build a nuclear power plant in Indonesia and explain the communication strategy in facing the rejection of nuclear energy utilization as a power plant in Indonesia. This research uses qualitative methods with data collection techniques through interviews with competent parties in the energy sector, especially nuclear energy and its utilization in power plants in Indonesia. The results showed that public acceptance of the nuclear power plant development plan experienced ups and downs depending on the time and events behind it. In addition, the interpretation of the phrase “considering nuclear as the last resort” in the legislation is also one of the obstacles to the progress of the implementation of nuclear power plant construction. Therefore, the support of all stakeholders is needed for the initiative to revise the laws and regulations that are considered to hinder the construction of nuclear power plants, in addition to building communication with those who reject the development plan through structured and massive persuasive and educational methods.